(untitled) (KMC Journal, 2022)
This article examines the intricate matrix of human and non-human relations to explore the symbolic essence of war of birds with the humanity in Alfred Hitchcock’s movie ‘The Birds’. This movie contains a plot in which nature strikes back to humanity. The everyday life is terrorized by the flocks of birds that attack people forcing them to think of their hostile relationship with other creatures. The study concentrates on exploring the reasons of havoc caused by the mute creatures, specially the birds that behave strangely. It analyses the film from an ecocritical insight envisioned by the theorists Arne Naess, Vandana Shiva, and Lawrence Buell. As it is a thematic interpretation of the movie, it reviews the scholarly comments of different critics and sets to explore the avian status quo struggle departing from the criticisms. Its finding suggests that anthropocentric hubris is the reason behind the dystopic state of the planet and the animals and birds are ultimately struggling for their own position on earth. It challenges the human claim that they are the most powerful creatures of this universe to keep everything under their control.